Представить произведение в виде многочлена: 1) (a-5)*(b+2) 2) (c+6)*(x-d) 3) (a^2+x)*(a-1) 4) (b-2)*(b^2+2b-3)
Представить произведение в виде многочлена: 1) (a-5)*(b+2) 2) (c+6)*(x-d) 3) (a^2+x)*(a-1) 4) (b-2)*(b^2+2b-3)
Ответ(ы) на вопрос:
решение во вложении))))))))))
[latex](a-5)*(b+2)=a*b+a*2-5*b-5*2=ab+2a-5b-10[/latex] [latex](c+6)*(x-d)=c*x+c*(-d)+6*x+6*(-d)=cx-cd+6x-6d[/latex] [latex](a^2+x)*(a-1)=a^2*a+a^2*(-1)+x*a+x*(-1)=a^3-a^2+ax-x[/latex] [latex](b-2)(b^2+2b-3)=b*b^2+b*2b+b*(-3)-2*b^2-2*2b-2*(-3)=b^3+2b^2-3b-2b^2-4b+6=b^3-7b+6[/latex]
Не нашли ответ?
Похожие вопросы